2020
DOI: 10.1111/jeb.13595
|View full text |Cite
|
Sign up to set email alerts
|

Limited mass‐independent individual variation in resting metabolic rate in a wild population of snow voles (Chionomys nivalis)

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…In the present study, the scaling coefficients for MMR and AAS were slightly higher than those calculated for SMR (Table 1), supporting the suggestion that MMR often scales isometrically with mass (reviewed in Glazier, 2009). Partitioning the allometric slopes into among-and within-individual components (Hagmayer et al, 2020) shows that both sources of variation contribute to the overall relationships in F. grandis (J.E.R., personal observations).…”
Section: Mass Effects On Aerobic Metabolismsupporting
confidence: 86%
“…In the present study, the scaling coefficients for MMR and AAS were slightly higher than those calculated for SMR (Table 1), supporting the suggestion that MMR often scales isometrically with mass (reviewed in Glazier, 2009). Partitioning the allometric slopes into among-and within-individual components (Hagmayer et al, 2020) shows that both sources of variation contribute to the overall relationships in F. grandis (J.E.R., personal observations).…”
Section: Mass Effects On Aerobic Metabolismsupporting
confidence: 86%
“…A low b e might also reflect short-term within-individual variation in factors that influence BM but not MR, such as gut content, hydration level and low-MR tissues (e.g. fat; Hagmayer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our focus in this study is on how a quantitative genetic perspective and (co)variance partitioning approach (e.g. Hagmayer et al, 2020) can increase our understanding of the evolution of metabolic scaling. Several quantitative genetic studies have already revealed that both MR and BM exhibit significant additive genetic variance (V A ; i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such approaches are unable to separate the traits under selection (i.e., body mass, SMR, or both; Hayes 2001; Hagmayer et al. 2020), they ignore the possibility of correlational selection, and they can involve doing “statistics on statistics” that can fail to propagate uncertainty and may result in statistical bias (Garcia‐Berthou 2001; Morrissey 2014). Measuring fitness can also be challenging and past studies have tended to rely on components thereof.…”
Section: Discussionmentioning
confidence: 99%